Hospital mortality of adults admitted to Intensive Care Units in hospitals with and without Intermediate Care Units: a multicentre European cohort study - Capuzzo, Maurizia; Volta, Carlo; Tassinati, Tania; Moreno, Rui; Valentin, Andreas; Guidet, Bertrand; Iapichino, Gaetano; Martin, Claude; Perneger, Thomas; Combescure, Christophe; Poncet, Antoine; Rhodes, Andrew; et al. (Critical care (London, England), 2014)
INTRODUCTION: The aim of the study was to assess whether adults admitted to hospitals with both Intensive Care Units (ICU) and Intermediate Care Units (IMCU) have lower in-hospital mortality than those admitted to ICUs without an IMCU. METHODS: An observational multinational cohort study performed on patients admitted to participating ICUs during a four-week period. IMCU was defined as any physically and administratively independent unit open 24 hours a day, seven days a week providing a level of care lower than an ICU but higher than a ward. Characteristics of hospitals, ICUs and patients admitted to study ICUs were recorded. The main outcome was all-cause in-hospital mortality until hospital discharge (censored at 90 days). RESULTS: One hundred and sixty-seven ICUs from 17 European countries enrolled 5,834 patients. Overall, 1,113 (19.1%) patients died in the ICU and 1,397 died in hospital, with a total of 1,397 (23.9%) deaths. The illness severity was higher for patients in ICUs with an IMCU (median Simplified Acute Physiology Score (SAPS) II: 37) than for patients in ICUs without an IMCU (median SAPS II: 29, P <0.001). After adjustment for patient characteristics at admission such as illness severity, and ICU and hospital characteristics, the odds ratio of mortality was 0.63 (95% CI 0.45 to 0.88, P = 0.007) in favour of the presence of IMCU. The protective effect of the IMCU was absent in patients who were admitted for basic observation, for example, after surgery (odds ratio 1.15, 95% CI 0.65 to 2.03, P = 0.630) but was strong in patients admitted to an ICU for other reasons (odds ratio 0.54, 95% CI 0.37 to 0.80, P = 0.002). CONCLUSIONS: The presence of an IMCU in the hospital is associated with significantly reduced adjusted hospital mortality for adults admitted to the ICU. This effect is relevant for the patients requiring full intensive treatment. TRIAL REGISTRATION: Clinicaltrials.gov NCT01422070. Registered 19 August 2011.
Keywords: senioři; pečovatelské domovy se zprostředkovatelskou péčí; senioři nad 80 let; Intensive Care Units; Europe; Cohort Studies; příjem pacientů; Evropa; Middle Aged; mužské pohlaví; mortalita v nemocnicích; kohortové studie; Aged, 80 and over; ženské pohlaví; Intermediate Care Facilities; Humans; jednotky intenzivní péče; nemocnice; lidé středního věku; Hospital Mortality; Patient Admission; Hospitals; Female; Aged; lidé; Male